Implications of bundled offerings for business development and competitive strategy in digital insurance - Fritzsche, Albrecht; Bohnert, Alexander (Geneva Papers on Risk and Insurance-Issues and Practice, 2021)
The ubiquitous availability of interconnected digital devices does not only change the kinds of risks that can be insured and the way insurance companies work, it also facilitates the formation of bundled offerings across different industrial sectors, including insurance as well as other products and services. We identify two distinct patterns in which such bundles change value creation in the insurance industry, which we describe as sales bundles and value bundles. In the former, the objects of insurance become more specific and risks can be estimated more precisely, but insurance becomes an add-on to other offerings at the point of sale. In the latter, insurance is merged with other products and services in comprehensive value bundles in which the exact distribution of responsibilities remains flexible. Although huge effort is required to establish these value bundles and maintain their systemic infrastructures, they create many new opportunities for business development in the insurance industry.
Created from Fastlane, Scopus look-up
Keywords: Digital innovation; Ecosystems; Platform economy; Risk management; Systems integration; Value networks